2003
DOI: 10.1038/sj.labinvest.3700004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a rapid-cycle PCR assay for the identification of the recurrent c.3421C>T mutation in the ABCC6 gene in pseudoxanthoma elasticum patients

Abstract: Pseudoxanthoma elasticum (PXE) is a heritable disorder of the connective tissue. Mutations in the ABCC6 gene could be linked to this disease and, just recently, the c.3421C4T mutation was also associated with a high risk of coronary artery disease. We have now developed new real-time PCR assays for the accurate and rapid determination of the c.3421C4T genotype. Using our new assay, we analyzed the presence of the c.3421C4T mutation in the largest collection of DNA samples from unrelated German PXE patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Among the 22 ABCC6 sequence variations found in this study, 17 had been previously described as PXE-causing mutations and ABCC6 polymorphisms [16, 19,22,23,24, 30, 35, 36], and 5 were novel DNA alterations resulting in the missense and silent variants p.Q655R, p.P664S, p.R1114C, p.G1311E and p.R1418R. An alignment using the ClustalW program showed that the missense mutations alter amino acid residues conserved in the human, mouse and rat MRP6 proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 22 ABCC6 sequence variations found in this study, 17 had been previously described as PXE-causing mutations and ABCC6 polymorphisms [16, 19,22,23,24, 30, 35, 36], and 5 were novel DNA alterations resulting in the missense and silent variants p.Q655R, p.P664S, p.R1114C, p.G1311E and p.R1418R. An alignment using the ClustalW program showed that the missense mutations alter amino acid residues conserved in the human, mouse and rat MRP6 proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 3 variants (p.R724K, p.V725V and p.I742V) had already been described as ABCC6 polymorphisms [36]. 14 DNA alterations had been shown to be PXE-causing mutations [16, 19,22,23,24, 30, 35, 36] and, consequently, have not been further examined in this study. Two ABCC6 sequence alterations were novel, namely the alterations p.R1114C and p.G1311E.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] To date, more than 120 PXE causing mutations have been identified. [3][4][5][6][7][8][9] The central hallmark of PXE is degenerative calcification with subsequent disintegration and destruction of elastic tissue in the skin, eyes, and cardiovascular system. PXE shows considerable clinical heterogeneity.…”
mentioning
confidence: 99%